Case report: A case of lateral neck mass: ectopic thyroid carcinoma or lymph node metastasis? - Xinran Wei; Ping Yu; Chengcheng Duan; Jingyue Zhong; Xianji Wu; Siqi Xiao; Wenxi Yu; Guang Zhang (Frontiers in Oncology)
ObjectiveTo review a rare case of a lateral neck mass pathologically confirmed as an encapsulated papillary thyroid carcinoma in our center for complementing the lack of management of rare cases, and to explore the differentiation of primary ectopic thyroid carcinoma and metastatic disease in the context of the presence of malignant tumors within the situ thyroid gland.MethodsWe searched for studies on lateral neck ectopic thyroid cancer to compare and analyze it with metastatic carcinoma of the thyroid gland in terms of clinical features, imaging manifestations, pathological features at molecular level, and treatment principles.ResultsBased on available data, we concluded that the mass of this patient was consistent with metastatic lateral neck ectopic thyroid carcinoma.ConclusionOur findings suggest that differentiating between these two conditions is challenging, as there is currently no reliable methods that can adequately determine their nature. Developing a preoperative diagnostic method would be significant for diagnosing pathologic masses in the lateral neck and selecting appropriate surgical extent and adjuvant therapy.